Clinical usefulness of nonhyperemic baseline Pd/Pa as a hybrid baseline Pd/Pa–fractional flow reserve strategy. Issue 1 (January 2015) - Kwon, Taek-Geun; Matsuzawa, Yasushi; Li, Jing; Aoki, Tatsuo; Guddeti, Raviteja R.; Widmer, R. Jay; Cilluffo, Rebecca R.; Lennon, Ryan J.; Lerman, Lilach O.; Lerman, Amir
Abstract : Objective: The ratio of basal distal intracoronary pressure (Pd) and aortic pressure (Pa) is a nonhyperemic index for the severity of coronary artery stenosis. The aim of the current study was to evaluate the clinical usefulness of a hybrid baseline Pd/Pa–fractional flow reserve (FFR) strategy in reducing the need for hyperemia. Methods: In this study, 570 lesions from 527 consecutive patients who had both baseline Pd/Pa and FFR determined were evaluated retrospectively. To evaluate the hybrid baseline Pd/Pa–FFR approach, patients were categorized into treatment, deferral, and undetermined groups on the basis of their baseline Pd/Pa. Thereafter, patients in the undetermined group were assigned to FFR-guided treatment or deferral on the basis of an FFR cutoff value of 0.80 or lower. Major adverse cardiac events were evaluated in a median of 48.8 months (interquartile range, 35.0–66.4). Results: A hybrid strategy using a deferral baseline Pd/Pa value of 1.00 (negative predictive value of 100%) and a treatment baseline Pd/Pa value of 0.86 or lower (positive predictive value of 100%), and limiting adenosine to a baseline Pd/Pa value between 0.87 and 0.99 would prevent the need for vasodilator drugs in 14.6% of lesions (14.0% patients), maintaining 100% agreement with an FFR-only strategy. However, adenosine-free lesions are increased to 59.6%, with 91% agreement. There was no difference in the major adverse cardiac event-free survival rate at 5 years between baseline Pd/Pa-guided and FFR-guided treatment patients (70.8 vs. 76.3%, P =0.63), or between baseline Pd/Pa-guided and FFR-guided deferral patients (71.3 vs. 82.4%, P =0.99). Conclusion: The current study reports a range of baseline Pd/Pa values that can predict myocardial ischemia without the need for inducing hyperemia. Adoption of this hybrid baseline Pd/Pa–FFR approach can reduce the need for drug-induced hyperemia.